2014
DOI: 10.1016/j.socscimed.2014.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Controlling parasites, understanding practices: The biosocial complexity of a One Health intervention for neglected zoonotic helminths in northern Lao PDR

Abstract: A parasitological survey in northern Lao PDR showed a remote ethnic minority village to be hyper-endemic for Taenia solium, a Neglected Tropical Disease (NTD) that impacts human and pig health. An intervention combining human Mass Drug Administration (MDA) with porcine vaccination and antihelmintic treatment was then implemented, targeting both T. solium and other soil-transmitted helminths. To understand the biosocial complexity of this integrated One Health intervention, we conducted a rapid ethnographic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(112 citation statements)
references
References 40 publications
2
106
0
4
Order By: Relevance
“…[25,28]. These studies found that a single dose of albendazole 400mg had a cure rate of approximately 50% against Taenia with the relatively low levels of hygiene and sanitation as described by Bardosh et al [19], the potential for cysticercosis in this close living community is considered to be extremely high, further validating the suspicion that a large number of residents currently suffer from cysticercosis [18].…”
Section: Impact Of Triple Dose Albendazole Treatment Against Taeniasismentioning
confidence: 77%
See 2 more Smart Citations
“…[25,28]. These studies found that a single dose of albendazole 400mg had a cure rate of approximately 50% against Taenia with the relatively low levels of hygiene and sanitation as described by Bardosh et al [19], the potential for cysticercosis in this close living community is considered to be extremely high, further validating the suspicion that a large number of residents currently suffer from cysticercosis [18].…”
Section: Impact Of Triple Dose Albendazole Treatment Against Taeniasismentioning
confidence: 77%
“…The village is homogenous for the Tai Dam ethnic group, an animistic culture which practises the consumption of raw pork associated with ancestral sacrificial ceremonies throughout the year [19]. Approximately 300 people (298 and 295 at the times of MDA) are dispersed amongst 60 households.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…These include poor hygiene and sanitation practices such as open defecation, lack of health hardware such as functioning latrines, lack of access to clean water, lack of basic education and knowledge on disease transmission, feeding human waste to pigs, ancestral sacrifices and consumption of raw pork, and lack of meat inspection practices at slaughter houses. 14,29,33,34 In addition, household contacts may acquire the infection through direct or indirect contact with carrier's feces, and clustering of neurocysticercosis cases around carriers has been further identified. 14,35 There have also been reports suggesting a link between cysticercosis and the use of human feces and "wastewater" for fertilizing crops.…”
Section: Risk Factors For Transmissionmentioning
confidence: 99%
“…29,34,72 In addition, poverty and religious beliefs prevail people's unwillingness to discard or cook cyst-infected meat, particularly during sacrificial ceremonies in certain communities. 33 Moreover, instead of interrupting the disease transmission, meat inspection practices may counterintuitively produce a negative impact by contributing to further economic losses in pig farmers through stigmatization, thereby forcing them to avoid the regulated markets and sell at a cheaper price directly to the lowest income earners.…”
Section: Control Strategies and Challengesmentioning
confidence: 99%